2013
DOI: 10.2172/1096459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volatile coatings on the morphology and optical detection of combustion-generated black carbon particles.

Abstract: We have measured time-resolved laser-induced incandescence (LII) from combustion-generated mature soot extracted from a burner and (1) coated with oleic acid or (2) coated with oleic acid and then thermally denuded using a thermodenuder. The soot samples were size selected using a differential mobility analyser and characterized with a scanning mobility particle sizer, centrifugal particle mass analyser, and transmission electron microscope. The results demonstrate a strong influence of coatings particle morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 111 publications
(168 reference statements)
12
31
0
Order By: Relevance
“…Numerous studies have shown that this aggregate morphology can become substantially compressed when the particles are coated with oxygenated hydrocarbons [48,[51][52][53][54][55][56][57][58][59][60][61] or sulfuric acid [21,56,[62][63][64]. This morphology restructuring may persist even when the coating is removed in a thermodenuder [51,53,55,56,60,63,64]. We recently showed that, for oleic acid coatings, the restructuring is largely reversible if the coating is removed by laser irradiation but is irreversible if the coating is removed in a thermodenuder [51].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that this aggregate morphology can become substantially compressed when the particles are coated with oxygenated hydrocarbons [48,[51][52][53][54][55][56][57][58][59][60][61] or sulfuric acid [21,56,[62][63][64]. This morphology restructuring may persist even when the coating is removed in a thermodenuder [51,53,55,56,60,63,64]. We recently showed that, for oleic acid coatings, the restructuring is largely reversible if the coating is removed by laser irradiation but is irreversible if the coating is removed in a thermodenuder [51].…”
Section: Introductionmentioning
confidence: 99%
“…Mature uncoated soot aggregates have a dendritic, branched-chain morphology described by a fractal dimension of *1.7 to 1.9 [40][41][42][43][44][45][46][47][48][49][50][51]. Numerous studies have shown that this aggregate morphology can become substantially compressed when the particles are coated with oxygenated hydrocarbons [48,[51][52][53][54][55][56][57][58][59][60][61] or sulfuric acid [21,56,[62][63][64].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the term "nascent" is used to refer to freshly emitted soot particles that have a negligible coating on the monomers. The diameter of these monomers varies in a range from 10 nm to more than 50 nm, depending on the fuel source and combustion conditions [4][5][6][7]. During the atmospheric processing, soot particles interact with organic and inorganic materials (in the form of aerosol or condensable vapors).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, China et al [8,43], using numerical simulations, predicted small changes in the absorption cross-section (a few percent), but a much more substantial change in the total scattering cross section (up to~300%) upon soot compaction. In addition to affecting the optical properties, changes in the soot structure can also affect the results of laser induced incandescence measurements [5]. Finally, the condensation of secondary organic matter preferentially takes place in empty pores on soot particles, and therefore, it is possible that compaction will affect secondary organic condensation on soot [44].…”
Section: Introductionmentioning
confidence: 99%